2005
DOI: 10.1103/physrevb.72.195116
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic coupling between nonmagnetic ions:Eu3+in EuN and EuP

Abstract: We consider the electronic structure of, and magnetic exchange (spin) interactions between, nominally nonmagnetic Eu 3+ ions (4f 6 , S=3, L=3, J=0) within the context of the rocksalt structure compounds EuN and EuP. Both compounds are ionic [Eu 3+ ; N 3− and P 3− ] semimetals similar to isovalent GdN. Treating the spin polarization within the 4f shell, and then averaging consistent with the J=0 configuration, we estimate semimetallic band overlaps (Eu 5d with pnictide 2p or 3p) of ∼ 0.1 eV (EuN) and ∼ 1.0 eV… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 32 publications
2
58
0
Order By: Relevance
“…The majority spin direct gap at X is quite similar in energy to the measured optical absorption edge. However, it is uncertain whether EuN could order ferromagnetically, 27 given the J = 0 ground state of the Eu 3+ ion, and our measurements have found no evidence for such ordering at the temperatures used for the optical spectroscopy. 33 We have previously shown that for GdN the optical absorption edge in the paramagnetic state is reasonably well described by taking an average of the spin-down and spin-up direct band gaps.…”
Section: Comparison Of Spectroscopies With Theorymentioning
confidence: 63%
See 2 more Smart Citations
“…The majority spin direct gap at X is quite similar in energy to the measured optical absorption edge. However, it is uncertain whether EuN could order ferromagnetically, 27 given the J = 0 ground state of the Eu 3+ ion, and our measurements have found no evidence for such ordering at the temperatures used for the optical spectroscopy. 33 We have previously shown that for GdN the optical absorption edge in the paramagnetic state is reasonably well described by taking an average of the spin-down and spin-up direct band gaps.…”
Section: Comparison Of Spectroscopies With Theorymentioning
confidence: 63%
“…[22][23][24][25][26] Of particular interest are the properties of EuN. 3,[27][28][29] The ground state of the Eu 3+ ion, the charge state anticipated when Eu bonds to nitrogen, has total angular momentum J = 0, so is non-magnetic. However, the separate spin and orbital angular momenta are both large, and thus it is possible that magnetic ordering could exist in the form of "hidden ferromagnetism".…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…So far there have only been two published calculations on europium monopnictides, to our knowledge. As previously noted, Horne et al reported EuN to be half-metallic based on the SIC-LSDA method [71] and was confi rmed by Johannes and Pickett [91] using the LSDA+ U scheme. Following Johannes and Pickett [91], using the LSDA + U approach with U and J set as 8 and 1 eV respectively, we have obtained similar band structures for EuN and EuP, as shown in fi gure 12.…”
Section: Eu Monopnictidesmentioning
confidence: 66%
“…The sensitivity of this Van Vleck susceptibility provides one means of detecting variation of the exchange coupling with pressure. [16] (iv) Other Related Work…”
Section: +mentioning
confidence: 99%